Clonostachys sp. Como promotor de crescimento vegetal em Soja - Castro, Jéssica Gomes de (Universidade Federal do Tocantins, 2021)
Soy is considered the main product of world agriculture and Brazil is the largest producer of soy in the world, for high productivity it is necessary to use efficient management techniques, aiming at this efficiency the use of biological products has been gaining prominence in the agricultural market. The use of growth-promoting fungi is widely used in seed inoculation, studies show that its use favors the culture positively in all its vegetative stage increasing its productivity. Therefore, the objective was to evaluate doses of Clonostachys sp. as a growth promoter in soybean culture. The experiment was carried out in a greenhouse at the Federal University of Tocantins - UFT, the experimental design used was the Fully Randomized Design (DIC), composed of a control and four doses of Clonostachys sp. (0, 4, 5, 6, 7 Kg-1 of seed) with four repetitions. The cultivar used in the experiment was 8644 IPRO. The fungus was obtained through the Agro-bio strain bank, it was transplanted in BDA medium and grown in autoclaved rice after fermentation, the substrate was mixed with graphite, sieved and a final product was obtained at a final concentration of 1x10 8 UFC ml. The parameters evaluated were plant height (AP), internode number (NE), root volume (VR), shoot dry mass (MSPA), number of pods per plant (NVP), number of grains per plant (NGP) , number of nodules (NN) seed weight per plant (PSP) and dry root mass (MSR). Results obtained statistically proved that there was a collaboration in the increase of BP in function of the evaluated doses of Clonostachys sp. where the microorganism proved to be a growth promoter in the dose 3,97 g Kg-1 of seed and in the parameters NVP and NGP both presented quadratic response, reaching its maximum of 48.33 pods per plant and 150.44 grains per plant in doses 3,90 Kg-1 of seed and 3.55 Kg-1 of seed respectively, thus proving its efficiency in increasing productivity. Therefore, it was found that Clonostachys sp. it has the potential to promote growth in soybean plants and increase productivity.